2010
DOI: 10.3354/meps08286
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected effects of starfish grazing on sandflat communities following an outbreak

Abstract: Starfish are significant determinants of community structure in marine ecosystems. The starfish Parvulastra (Patiriella) exigua is normally found on intertidal rocky shores. We examined a major outbreak of this species in Langebaan Lagoon, a marine embayment on the west coast of South Africa, and the only known soft-sediment ecosystem where P. exigua flourishes. We document this outbreak and describe subsequent field caging experiments testing the influence of this starfish on soft-sediment community structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
23
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 42 publications
2
23
1
Order By: Relevance
“…One possible explanation for this is that increasing grazing pressure caused a shift in size of microalgae, with individuals becoming larger. The lack of an effect on microalgal biomass is surprising, as several studies have reported grazer-induced reductions in chl a levels (Jackson et al 2009, Pillay et al 2009, 2010a.The most significant finding arising from the present study was the enhancement of EPS levels on the sediment surface with increasing densities of Parvulastra exigua. This ability of P. exigua may be due to 2 mechanisms.…”
contrasting
confidence: 58%
See 4 more Smart Citations
“…One possible explanation for this is that increasing grazing pressure caused a shift in size of microalgae, with individuals becoming larger. The lack of an effect on microalgal biomass is surprising, as several studies have reported grazer-induced reductions in chl a levels (Jackson et al 2009, Pillay et al 2009, 2010a.The most significant finding arising from the present study was the enhancement of EPS levels on the sediment surface with increasing densities of Parvulastra exigua. This ability of P. exigua may be due to 2 mechanisms.…”
contrasting
confidence: 58%
“…The addition of bacteria to faeces of P. exigua may also enhance bacterial growth on sediment (Hargrave 1970). Microalgal exudates are unlikely to contribute to the elevation of EPS levels recorded in the present study, as P. exigua had negative effects on microalgal abundance and no effect on biomass.The hump-shaped unimodal relationship recorded between densities of Parvulastra exigua and microalgal richness and diversity has also been recorded in experimental tests of this starfish on soft-sediment macrofauna (Pillay et al 2010a). Unimodal effects on diversity have been recorded in studies of various other grazers in marine ecosystems (Paine & Vadas 1969, Lubchenco 1978.…”
mentioning
confidence: 60%
See 3 more Smart Citations